Case report: Left gaze and facial nerve palsies after ventral intermediate thalamic nucleus deep brain stimulation implantation - Cegielski, Victoria; Gratton, Sean (Frontiers in Neurology, 2023)
Deep brain stimulation (DBS) to the ventral intermediate nucleus (VIM) of the thalamus has become a common procedure for some refractory, medication-resistant movement disorders like essential tremors. The most common adverse effects from this surgery include dysarthria and gait disturbances. This case report details a left gaze and ipsilateral facial nerve palsy following overshot cannula insertion into the pons during a VIM DBS procedure. Initial patient presentation after surgery revealed significant impairment of horizontal gaze to the left. This improved during follow-up visits and after the recession of the bilateral medial recti. When considering complications of the VIM DBS procedure, surgeons should be aware of the risks of cannula overshot given the anatomic proximity between the thalamus and brainstem. Furthermore, patients should be aware of this risk when making their surgical decision. All patients who undergo VIM DBS should be assessed for cranial nerve deficits after placement.